Strategi Komunikasi Pemasaran Trans TV dengan Menggunakan Meta Ads dalam Meningkatkan Brand Awareness - Marliana, Dina (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2023)
Television business competition in the digital era is very tight. Therefore the marketing team must have a strategy to increase brand awareness. Trans TV is one of the television stations that can still maintain its existence even in the new media era. To remain reliable television, Trans TV uses Integrated Marketing Communication. By combining social media as well as mainstream media to increase consumers on the brand. One way is to use Meta Ads where awareness is one of the objective points. This study used a qualitative research method in which the data were obtained through observation and interviews. The results of the study show that using Meta Ads can increase brand awareness. Increased brand awareness to the cognitive level of consumers can also be seen from the reach achieved from advertisements posted on Instagram social media through Meta Ads.